Comparison of annexin II, p63 and α-methylacyl-CoA racemase immunoreactivity in prostatic tissue: a tissue microarray study. Issue 7 (17th August 2006) - Stewart, Jocelyn; Fleshner, Neil; Cole, Heather; Sweet, Joan
Abstract : Background: Current ancillary markers for diagnosis in prostate biopsies include p63 and α-methylacyl-CoA racemase (AMACR). Annexin II (ANXII), a calcium and phospholipid binding protein, is lost in prostate cancer. Aims: To investigate ANXII expression in order to assess its utility as a novel diagnostic marker in comparison to p63 and AMACR. Methods: Using immunohistochemistry on six tissue microarrays, ANXII, p63, and AMACR expression was analysed from 210 radical prostatectomy cases. Staining was evaluated in benign and atrophic glands, high-grade prostatic intraepithelial neoplasia (HGPIN), and prostatic adenocarcinoma. Separate scores were given for ANXII, AMACR and p63 expression. Results: Diffuse cytoplasmic expression of ANXII correlated with p63 reactivity in basal cells. Benign glands were positive for ANXII in 286/292 cores (98%) and negative for AMACR in all 292 cores. HGPIN showed heterogeneous expression of AMACR and ANXII. A significantly larger proportion of HGPIN glands were correctly identified as ANXII negative than as positive for AMACR. ANXII loss in prostate cancer was found in 282/320 cores (88%) and correlated with positive AMACR expression (272/320 cores, 85%), which was not statistically significant. There was no statistically significant correlation between ANXII scores and the clinical parameters examined. Conclusions: Immunohistochemical staining for ANXII is a consistent and reliable marker of prostatic neoplasia. The findings of this study suggest the potential utility of ANXII as a diagnostic aid in prostate cancer histopathology.